High Genetic Diversity of Plasmodium vivax on the North Coast of Papua New Guinea - Arnott, Alicia (The American Society of Tropical Medicine and Hygiene, 2013)
Despite having the highest Plasmodium vivax burden in the world, molecular epidemiological data from Papua New Guinea (PNG) for this parasite remain limited. To investigate the molecular epidemiology of P. vivax in PNG, 574 isolates collected from four catchment sites in East Sepik (N = 1) and Madang (N = 3) Provinces were genotyped using the markers MS16 and msp1F3. Genetic diversity and prevalence of P. vivax was determined for all sites. Despite a P. vivax infection prevalence in the East Sepik (15%) catchments less than one-half the prevalence of the Madang catchments (27–35%), genetic diversity was similarly high in all populations (H(e) = 0.77–0.98). High genetic diversity, despite a marked difference in infection prevalence, suggests a large reservoir of diversity in P. vivax populations of PNG. Significant reductions in transmission intensity may, therefore, be required to reduce the diversity of parasite populations in highly endemic countries such as PNG.